Plasma ion heating by cryogenic pellet injection. (February 2019) - Aleynikov, Pavel; Breizman, Boris N.; Helander, Per; Turkin, Yuriy
Abstract : The injection of cryogenic pellets into a magnetically confined plasma is shown to be accompanied by a considerable transfer of thermal energy from the electrons in the background plasma to the ions. The resulting ion heating can be significant, particularly in plasmas with disparate electron and ion temperatures, and can affect the energy balance of the plasma. In recent Wendelstein 7-X experiments, this mechanism can account for a substantial fraction of the ion heating power during pellet injection.